Effect of natural ageing on the properties of recycled polypropylene/ethylene vinyl acetate/wood flour composites - Silva,Caroline Barbosa da (2017)
ABSTRACT Wood flour composites main applications are represented by outdoor furnishing. Therefore, it is important to evaluate their behavior under natural ageing conditions. This work aims to investigate the natural ageing impact on the mechanical, physical, thermal e morphological properties of recycled polypropylene/ethylene vinyl acetate/wood flour composites (PP/EVA/ITA). Samples were exposed to natural ageing for 12 months in Porto Alegre (BR). Mezilaurus itauba (ITA) wood flour was used at 30 % w/w. Results showed that PP filled wood flour retained a higher fraction of the original mechanical properties after natural ageing. Crystallinity degree for composites increased from 30.9 up to 37.5% Climatic conditions affected the colorimetric and morphological characteristics of composites, indicating that there was not only photo-degradation but also thermo-oxidative and hydrolytic degradation. In this way, the use of antioxidant additives and UV photo-absorbers is recommended to avoid stress-cracking, discoloration and loss the mechanical properties.